The Dynamics of Fair Trade as a Mixed-form Market - Becchetti, Leonardo (Journal of business ethics, 2008)
This article analyses the Fair Trade sector as a “mixed-form market,” i.e., a market in which different types of players (in this case, nonprofit, co-operative and for-profit organizations) coexist and compete. The purposes of this article are (1) to understand the factors that have led Fair Trade to become a mixed-form market and (2) to propose some trails to understand the market dynamics that result from the interactions between the different types of players. We start by defining briefly Fair Trade, its different dimensions (including the “fair” quality of the products) and its organizational landscape, focusing on the distinction between the pioneer “Alternative Trading Organizations” and the second-mover companies. Then, we recall the theoretical emergence factors for each type of organization (nonprofit, co-operative and for-profit) and apply these emergence factors to the context of Fair Trade. This analysis allows us to capture the specificities of each type of operator with regard to Fair Trade and, thus, to have a better understanding of the dynamics in the sector. Such dynamics includes competition, but also conflict and partnership. Our analysis includes elements on ethical imitation, consumers’ behaviors, effects on welfare and the role of the government.